The Species Problem Ongoing Issues - Pavlinov, Igor Ya (IntechOpen, 2013)
The book includes collection of theoretical papers dealing with the species problem, which is among most fundamental issues in biology. The principal topics are: consideration of the species problem from the standpoint of modern non-classical science paradigm, with emphasis on its conceptual status presuming its analysis within certain conceptual framework; evolutionary emergence of the species as discrete unit of certain level of generality; epistemological consideration of the species as a particular explanatory hypotheses, with respective revised concepts of biodiversity and conservation; considerations of evolutionary and phylogenomic species concepts as candidates for the universal one; re-appraisal of the biological species concept based on the "friend-foe" recognition system; species delimitation approach using multi-locus coalescent-based method; a re-consideration of the Darwin's species concept.